2017
DOI: 10.1212/wnl.0000000000004500
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography identifies outer retina thinning in frontotemporal degeneration

Abstract: FTD is associated with outer retina thinning, and this thinning correlates with disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 41 publications
5
67
0
Order By: Relevance
“…When comparing thicknesses for particular retinal layers, it is important to consider that the algorithm used could affect the thickness measurements, and it is useful to know absolute value differences. Using Spectralis to compare patients with FTD and controls, we found that our results agree with previous findings that used IRA 3.6 and showed outer retina thinning in patients . The outer retina was thinner in patients than controls by 5.7 μm using Spectralis, which is greater than the difference in outer retina thickness between IRA 3.6 and Spectralis (1.6 μm).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…When comparing thicknesses for particular retinal layers, it is important to consider that the algorithm used could affect the thickness measurements, and it is useful to know absolute value differences. Using Spectralis to compare patients with FTD and controls, we found that our results agree with previous findings that used IRA 3.6 and showed outer retina thinning in patients . The outer retina was thinner in patients than controls by 5.7 μm using Spectralis, which is greater than the difference in outer retina thickness between IRA 3.6 and Spectralis (1.6 μm).…”
Section: Discussionsupporting
confidence: 90%
“…While the literature shows that advances in segmentation algorithms have emerged every few years, the algorithms we evaluated have been used in recently published cross‐sectional and longitudinal studies, and these algorithms will likely continue to be used for some time . However, it is remarkable that our study found no errors to manually correct with IRA 3.8.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Garcia-Martin et al 23 showed that not only were inner retinal layers reduced in AD, but the outer retinal layers were also impaired. Moreover, Kim et al 24 reported that frontotemporal degeneration is associated with outer retinal thinning, and this thinning correlates with disease severity. Considering these OCT findings of neurodegenerative disorders, one possibility is that the retina is vulnerable to the same neuroinflammatory injury that causes neurodegenerative disease in the brain, and similar mechanisms may play a role in the pathogenesis of AMD and AD, 4,25 in which the serum level of BDNF has been shown to be affected.…”
Section: Discussionmentioning
confidence: 99%